(untitled) (Sociología y tecnociencia, 2021)
The outbreak of Covid-19 has put serious pressure on the management of international tourism problems and Indonesia, being a tourist attraction, is not an exception. In this wake, the main purpose of this study was to analyze the dilemma of Indonesia’s health policy in maintaining the stream of tourism visitors as well as containing the spread of the Covid-19 pandemic. Qualitative research methods were used in this research. Data collection was conducted through constitutional legislations, press releases from the Indonesian Covid-19 special task force and observations gathered from numerous public facilities which are mostly used by travellers such as airport, train and bus station. This research reveals that that the policy prioritizing to the safety of economic growth and tourism in the global pandemic context is inclined to be more contra-productive to the management of containing contagion. It was also found that the implementation of health protocols and restrictions on social activities is also claimed to be the most and efficient way to contain the contagion.